Computer-Based Monitoring and Remote Controlling for Oil Well Pumps Using Scada - Tjiptadi, Rudi (Bina Nusantara University, 2011)
The research aims to change manually the monitoring and controlling of oil well pumps into a computer-based system using SCADA (Supervisory and Data Acquisition) system. To design the protection system which consists of controller unit and display system, RTU (Remote Terminal Unit) and MTU (Master Terminal Unit) are used. The research results in a controller unit which is able to communicate to personal computer using RS-232 C and an alarm system to protect oil pump motors by detecting sensors installed at the pumps.